My life as a ninja - Tashjian, Janet (Tashjian, Janet. My life series., 2019)
Derek and his friends Carly, Matt, and Umberto enjoy learn about ninja culture. When someone starts vandalizing their school, the friends set out to find out who is responsible, but their efforts might result in the ultimate embarrassment for Derek.